Excess Volatility and the Asset-Pricing Exchange Rate Model with Unobservable Fundamentals - Giorgianni, Lorenzo (IMF Working Papers; Working Paper, 1999)
This paper presents a method to test the volatility predictions of the textbook asset-pricing exchange rate model, which imposes minimal structure on the data and does not commit to a choice of exchange rate 'fundamentals.' Our method builds on existing tests of excess volatility in asset prices, combining them with a procedure that extracts unobservable fundamentals from survey-based exchange rate expectations. We apply our method to data for the three major exchange rates since 1984 and find broad evidence of excess exchange rate volatility with respect to the predictions of the canonical asset-pricing model in an efficient market.